Atomically dispersed nickel–nitrogen–sulfur species anchored on porous carbon nanosheets for efficient water oxidation - Hou, Yang; Qiu, Ming; Kim, Min Gyu; Liu, Pan; Nam, Gyutae; Zhang, Tao; Zhuang, Xiaodong; Yang, Bin; Cho, Jaephil; Chen, Mingwei; Yuan, Chris; Lei, Lecheng; et al. (Nature communications, 2019)
Developing low-cost electrocatalysts to replace precious Ir-based materials is key for oxygen evolution reaction (OER). Here, we report atomically dispersed nickel coordinated with nitrogen and sulfur species in porous carbon nanosheets as an electrocatalyst exhibiting excellent activity and durability for OER with a low overpotential of 1.51 V at 10 mA cm −2 and a small Tafel slope of 45 mV dec −1 in alkaline media. Such electrocatalyst represents the best among all reported transition metal- and/or heteroatom-doped carbon electrocatalysts and is even superior to benchmark Ir/C. Theoretical and experimental results demonstrate that the well-dispersed molecular S|NiN x species act as active sites for catalyzing OER. The atomic structure of S|NiN x centers in the carbon matrix is clearly disclosed by aberration-corrected scanning transmission electron microscopy and synchrotron radiation X-ray absorption spectroscopy together with computational simulations. An integrated photoanode of nanocarbon on a Fe 2 O 3 nanosheet array enables highly active solar-driven oxygen production. Water oxidation is considered the bottleneck reaction for light-driven water splitting due to the sluggish kinetics and poor stability. Here, authors show metal- and heteroatom-doped carbons as effective catalysts for both electrochemical and photoelectrochemical water splitting.